STUDY OF PATTERN OF RIB FRACTURE IN VICTIMS OF TWO WHEELERS DUE TO ROAD TRAFFIC ACCIDENTS - AUTOPSY BASED STUDY (Journal of Forensic Medicine & Toxicology, 2020)
Road traffic accidents shares major burden of magnitude of mortality in both developing and developed countries. The humans became the victim of damages of his own invention by means of road traffic accidents. Most of the time, pattern of skeletal injuries to the surrounding soft tissues and/ or vital organs, like the skull fracture causing injury to the brain, fracture of ribs piercing the heart or lung, fracture of long bones leading to hemorrhage due to rupture of large vessels with other injuries would help in the reconstruction of road traffic accident by two-wheeler.The current study is under taken to analyze the pattern of rib cage fractures due to two wheeler accidents with respect to site, situation, number, size, severity and extent which helps in reconstruction of manner and also cause of death. This study is an attempt to help the law enforcement authorities and policy makers regarding road safety measures and need for trauma care system even at the remote places.
Keywords: Ribcage fracture; rib fractures; chest bone fracture